2004
DOI: 10.1021/ol0494360
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Enamides via Palladium(II)-Catalyzed Vinyl Transfer from Vinyl Ethers to Nitrogen Nucleophiles

Abstract: Palladium(II) complexes catalyze the formation of enamides via the formal cross-coupling reaction between nitrogen nucleophiles and vinyl ethers. These vinyl transfer reactions proceed in good yields with amide, carbamate, and sulfonamide nucleophiles, and the optimal catalyst is (DPP)Pd(OCOCF(3))(2) (DPP = 4,7-diphenyl-1,10-phenanthroline). [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(37 citation statements)
references
References 51 publications
0
36
0
1
Order By: Relevance
“…Systematic investigations revealed that a base, for example, potassium carbonate or hydroxide, is essential, whereas the alcohol can be replaced by water (entries [5][6][7][8][9]. This goes along with reports in the literature that phosphines themselves can act as reducing agents for transition metals, a process assisted by water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic investigations revealed that a base, for example, potassium carbonate or hydroxide, is essential, whereas the alcohol can be replaced by water (entries [5][6][7][8][9]. This goes along with reports in the literature that phosphines themselves can act as reducing agents for transition metals, a process assisted by water.…”
mentioning
confidence: 99%
“…They promise to be valuable alternatives to traditional syntheses, for example, from carbonyl compounds and amides [6] or from hydroxylamines and carboxylic anhydrides, [7] that usually require harsh conditions and give (E/Z)-mixtures, and to metal-catalyzed coupling reactions of amides with vinyl halides, pseudohalides [8] or ethers, [9] which suffer from limited substrate availability.…”
mentioning
confidence: 99%
“…Traditional syntheses-for example, from carbonyl compounds and amides [12] or from hydroxylamines and acetic anhydride [13] -require harsh conditions and yield mixtures of E/Z products. Metal-catalyzed coupling reactions of vinyl halides, [14] vinyl triflates, [15] or vinyl ethers [16] proceed under milder conditions but suffer from the limited availability of these substrates.…”
mentioning
confidence: 99%
“…34 was transformed into 35 using the same method as in the case of 28. After for- 55) ring-closing metathesis was performed in the presence of 30, affording cyclic compound 37. Introduction of a hydroxyl group followed by oxidation of the resulting crude lactamol with PCC gave the known lactam (R)-(ϩ)-38.…”
Section: Asymmetric Allylic Alkylation Using Nitromethane As the Nuclmentioning
confidence: 99%